MODELLING OF DYNAMIC ASPECTS OF OPERATION IN RAILWAY VEHICLE TRACTION DRIVE SYSTEM INCLUDING THE ELECTROMECHANICAL COUPLING - Robert KONOWROCKI (Scientific Journal of Silesian University of Technology. Series Transport)
In this paper, the influence of electromechanical interaction in an electric motor on the railway vehicle driving system dynamics was investigated. This is the train driven by DC. In particular, there is considered influence of electromagnetic field between a rotor and stator on excitation of resonant torsional vibrations of the drive system. Conclusions drawn from the computational results can be very useful during the design phase of these devices as well as helpful for their users during regular maintenance.